On the typification of Bolanthus cherlerioides (Bornm.) Bark. (Caryophyllaceae) - Yildizbaş, Avni; Koç, Murat (Phytotaxa, 2018)
The genus Bolanthus (Ser.) Rchb. (1841: 205) (Caryophyllaceae Juss.) includes 24 taxa mostly occurring along the coasts of eastern Mediterranean regions (Syria, Lebanon, Palestine, Greece, Isreal, and Turkey) (Barkoudah 1962). The genus is represented by 8 taxa in the Europaean flora and by 6 taxa in Syria, Palestine, Isreal and Lebanon (Barkoudah 1962, Zohary 1966, Barkoudah 1993). All of the taxa that are distributed in Europe are known from Greece and East Aegean Islands, Phitos (1997).